186 Degree of Midline Shift at Presentation Affects Long-Term Outcomes in Cases of Traumatic Brain Injury: A Secondary Analysis of the Phase 3 COBRIT Clinical Trial. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Puffer, Ross; Yue, John K; Mesley, Matthew; Billigen, Julia; Sharpless, Jane; Fetzick, Anita L; Puccio, Ava; Diaz-Arrastia, Ramon; Okonkwo, David O
Abstract: INTRODUCTION: Following traumatic brain injury (TBI), midline shift is often caused by space occupying lesions leading to increased intracranial pressure and worsened morbidity and mortality. Outcome has been studied in this population; recovery trajectory in these patients has not been reported. We utilized the COBRIT trial to analyze subject recovery over time depending on degree of midline shift at presentation. METHODS: Subject data from the COBRIT trial were stratified into groups of midline shift, and outcome measures were analyzed at 30, 90, and 180 d after injury. Recovery trajectory analysis was performed identifying patients with outcome measures at all time points, analyzing the degree of recovery based on midline shift at presentation. RESULTS: There were 896, 1196, and 895 subjects with adequate outcome data at 30, 90, and 180 d, respectively. Rates of favorable outcome (GOS-E 4-8) at 6 mo after injury were 87% (no midline shift), 79% (1-5 mm shift), 64% (6-10 mm shift), and 47% (>10 mm shift). The mean improvement from unfavorable outcome (GOS-E 2-3) to favorable outcome (GOS-E 4-8) from 1 to 6 mo in all groups was 20%. The mean GOS-E of subjects in the 6 to 10 mm group crosses from unfavorable outcome into favorable outcome at 90 d, and the mean GOS-E of subjects in the >10 mm group nearly reaches the threshold of favorable outcome by 180 d after injury. CONCLUSION: In this secondary analysis of the COBRIT trial, TBI subjects with <10mm of midline shift on admission head CT had significantly improved functional outcomes through 180 d after injury compared to those with greater than 10 mm of midline shift; however, nearly 50% of patients with 10 mm of midline shift will achieve a favorable outcome (GOS-E 4-8) by 6 mo after injury. Subjects with a unfavorable outcome (GOS-E 2-3) at 30 d should continue close observation as approximately 20% will improve to a favorable outcome by 6 mo after injury.